2020
DOI: 10.1021/acs.joc.9b03322
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Group-Controlled Remote Regioselective Electrophilic Aromatic Halogenation Reactions

Abstract: Being able to utilise a protecting group to influence remote regiocontrol offers a simple alternative approach to direct late-stage functionalisation of complex organic molecules. However, protecting groups that have the ability to influence reaction regioselectivity remote to their local chemical environment are not widely reported in the literature. Herein, we report the development of remote regioselective electrophilic aromatic substitution (S E Ar) reactions that are enabled via the application of the tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Protecting group controlled remote C(sp 2 -H) iodination was reported by Brittain and Cobb in arene systems (Scheme 34). [46] In their protocol, tetrafluoropyridyl (TFP) group was used to protect a phenolic À OH group present in the substrate (53). The said protecting group controls the regioselctivity of the iodination resulting in iodinesubstitution at a position not easily accessible by classical electrophilic substitution.…”
Section: It Was Found That a Direct Oà H Arylation And Cà H Iodinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Protecting group controlled remote C(sp 2 -H) iodination was reported by Brittain and Cobb in arene systems (Scheme 34). [46] In their protocol, tetrafluoropyridyl (TFP) group was used to protect a phenolic À OH group present in the substrate (53). The said protecting group controls the regioselctivity of the iodination resulting in iodinesubstitution at a position not easily accessible by classical electrophilic substitution.…”
Section: It Was Found That a Direct Oà H Arylation And Cà H Iodinationmentioning
confidence: 99%
“…[hmim]Br DCDPH,NBS Chiral Organocatalyst [56] K 2 S 2 O 8 TBAX or NXS [85] (Cl/Br/I) Electrochemical [74] Acyl chloride [91] NXS (X=Br/Cl/I) AlCl 3 /NXS PIDA (X=Br/Cl) NIS,TFA [46] ArI(OAc) 2 [43] PIDA/NaX [76] (X=Cl/Br/I) NaX NFSI [92] (X=Br/I) NaI,Electrolysis [101] TBAB or TBAC [52] (Pummerer) Erythrosin B, NBS,LED [22] PhI(OAc) 2 or K 2 S 2 O 8 NaBr [38] TXCA [102] ChemistrySelect material in case of mono C-5 halogenation in presence of TEMPO possibly indicated that the NXS was being captured by TEMPO preventing subsequent halogenation. N-flurobenzenesulfonimide (NFSI) was used as an oxidant and sodium salts of halogens (bromine and iodine) acted as halogen source for the halogenation of quinolines (137)and arenes.…”
Section: General Halogenation On Heteroarene Systems Using Different ...mentioning
confidence: 99%
“…This amino acid was shown to be readily incorporated into peptides, and further it was disclosed that through the addition of a thiol and a fluoride source, the TFP group could be easily removed to give free phenolic tyrosine. The TFP ring was also shown to have profound electronic implications [ 72 , 73 ].
Scheme 14 Synthesis of tetrafluoropyridyl amino acids, Cobb and co-workers [ 70 , 72 ].
…”
Section: Complex Fluorine-containing Aromatic Amino Acidsmentioning
confidence: 99%
“…Halo-arene synthesis by EAS strategy is an essential guiding reaction for understanding the reactivity and functionalization of aromatics. [6][7][8] Halo-arenes frequently occur in pharmaceuticals and agrochemicals as essential functional molecule [9] (Scheme 1B). Therefore, halogenated aromatic amino acids represent an important class of building blocks, which have been utilized for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…ortho to the phenolic hydroxyl group in tyrosine to yield the formation of thyroxine [2–5] (Scheme 1A). Halo‐arene synthesis by EAS strategy is an essential guiding reaction for understanding the reactivity and functionalization of aromatics [6–8] . Halo‐arenes frequently occur in pharmaceuticals and agrochemicals as essential functional molecule [9] (Scheme 1B).…”
Section: Introductionmentioning
confidence: 99%